Students’ birth date and academic progression - Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro (My University, 2019)
Education laws which impose starting cut-off dates for students to begin compulsory education may be negative for those students who are born just before these cut-offs; this is because these students will be among the youngest in their classroom, while those born just after (the oldest students) will see their academic achievement increased. The current research works on this subject employing census and longitudinal data for the most populated region of Spain (Andalusia), making use of a regression discontinuity methodology. We find that the youngest students in the classroom (due to this school entry cut-off) present lower academic achievement compared to the oldest students, being this effect reduced while students progress in their education. This motivates policy interventions aimed at giving the option to parents to choose whether or not to delay their children’s access to school when the latter are too young.
Keywords: Estudiantes - Aprendizaje - Andalucía; Estudiantes - Rendimiento; Estudiantes - Adaptación; birth date; regression discontinuity; students’ progression; Andalusia